Neuromuscular and Functional Responses Among Males Trained with Free Weights vs. Machines: Implications for Injury Prevention - Alex Souto Maior; Marco Leandro Martins de Assis (International Universities Strength and Conditioning Association, 2023)
The purpose of this study was to compare balance, functional performance and isometric hip strength muscle among males practitioners of resistance training (RT) with Free-weights and Machines. Thirty males were recruited and separated into two groups: Free-weights (n = 15) and Machines (n = 15). Free-weights group showed a routine of RE that engaged the whole body with resistance bands, free-weights, dumbbells, and medicine balls. Conversely, machine group trained only exercises on machines. All participants underwent three tests to assess balance, functionality, and isometric muscle strength. All tests were performed in a single assessment session in the following order: Y Balance test; functional performance testing; and maximal isometric hip strength, respectively. The two-way ANOVA yielded main effects for group in the anterior (F1,22= 12.11, p < .002), posteromedial (F1,22= 16.87, p < .0005), posterolateral (F1,22= 15.97, p < .0006) and composite (F1,22= 21.39, p < .0001) in performance during YBT between free-weight vs. machines group for both legs. Single leg step down (SLSD) and Single leg hop (SLH) test demonstrating better functional performance in the free-weight group for both legs (p<.001). Isometric muscle strength of hip abduction and extension showed lower in the machines when compared to free-weight group for both legs. This study showed greater balance, functional performance and isometric muscle strength of hip abduction and extension in males trained with Free-weight. Males trained with machine showed lower functional performance, balance and bilateral asymmetry of the hip extensor muscles strength and risk of injuries.